An Analysis of the Macroeconomic Determinants of Entrepreneurial Activity in Turkey - Dom Tomak, Serpil (International Journal of Economics and Financial Issues, 2018)
Today, entrepreneurship is seen as the main element of economic growth plays an important role in national economies in terms of contribution to employment innovation creation. In this sense, it is also important to determine the basic elements that affect entrepreneurial activities, to support the creation development of new businesses to decision makers for taking necessary measures. In this study, the effects of some macroeconomic factors on the dynamics of entrepreneurial activity in Turkey are investigated for a period of 11 years (2007-2017). The research includes access to credit (ACC), economic confidence index (ECI), inflation rate (INF), foreign direct investment (FDI), unemployment rate (UNEMP) industrial production index (IPI). The results of the research demostrate that there is no correlation between access to credit, economic confidence index unemployment rate entrepreneurship level; whereas inflation rate, foreign direct investment, industrial production index are related for the period covered in Turkey. Keywords: Determinants of entrepreneurship, entrepreneurial activities, Turkey. JEL Classifications: L25, L26, M13